The phylogeny of the Casque‐headed Treefrogs (Hylidae: Hylinae: Lophyohylini). (27th March 2020) - Blotto, Boris L.; Lyra, Mariana L.; Cardoso, Monica C.S.; Trefaut Rodrigues, Miguel; R. Dias, Iuri; Marciano‐Jr, Euvaldo; Dal Vechio, Francisco; Orrico, Victor G.D.; Brandão, Reuber A.; Lopes de Assis, Clodoaldo; Lantyer‐Silva, Amanda S.F.; Rutherford, Mike G.; et al.
Abstract: The South American and West Indian Casque‐headed Treefrogs (Hylidae: Hylinae: Lophyohylini) include 85 species. These are notably diverse in morphology (e.g. disparate levels of cranial hyperossification) and life history (e.g. different reproductive modes, chemical defences), have a wide distribution, and occupy habitats from the tropical rainforests to semiarid scrubland. In this paper, we present a phylogenetic analysis of this hylid tribe based on sequence fragments of up to five mitochondrial ( 12S, 16S, ND1, COI, Cytb ) and six nuclear genes ( POMC, RAG‐1, RHOD, SIAH, TNS3, TYR ). We included most of its species (> 96%), in addition to a number of new species. Our results indicate: (i) the paraphyly of Trachycephalus with respect to Aparasphenodon venezolanus ; (ii) the nonmonophyly of Aparasphenodon, with Argenteohyla siemersi, Corythomantis galeata and Nyctimantis rugiceps nested within it, and Ap. venezolanus nested within Trachycephalus ; (iii) the polyphyly of Corythomantis ; (iv) the nonmonophyly of the recognized species groups of Phyllodytes ; and (v) a pervasive low support for the deep relationships among the major clades of Lophyohylini, including C. greeningi and the monotypic genera Itapotihyla and Phytotriades . To remedy the nonmonophyly of Aparasphenodon, Corythomantis, and Trachycephalus, we redefined Nyctimantis to include Aparasphenodon (with the exception of Ap. venezolanus, which we transferred to Trachycephalus ), Argenteohyla, and C. galeata . Additionally, our results indicate the need for taxonomic work in the following clades: (i) Trachycephalus dibernardoi and Tr. imitatrix ; (ii) Tr. atlas, Tr. mambaiensis and Tr. nigromaculatus ; and (iii) Phyllodytes . On the basis of our phylogenetic results, we analyzed the evolution of skull hyperossification and reproductive biology, with emphasis on the multiple independent origins of phytotelm breeding, in the context of Anura. We also analyzed the inter‐related aspects of chemical defences, venom delivery, phragmotic behaviour, co‐ossification, and prevention of evaporative water loss.